Feasibility Analysis of Income From White Coconut Meat Processing Among Coconut Farmers in Polewali Village North Mamuju Regency - Ainul Hikmah Gandali; Abdul Kahar; Mustamin Mustamin; Sugianto Sugianto (Journal of Accounting and Finance Management, 2026)
This study will explore and describe in depth the white copra processing activities of coconut farmers in Polewali Village, North Mamuju Regency, in an effort to assess income feasibility and support appropriate business decision-making. This study uses a qualitative approach to analyze and assess the feasibility of MSMEs as a context that needs to be analyzed in depth to provide MSMEs with a complete picture of their business feasibility indicators. The research results obtained findings that the white copra processing business was declared feasible to run, because it was able to generate net profits and produce an R/C ratio value of 1.15, more than 1. This shows that each cost expenditure in the production process can generate additional income of 0.15 so that it can increase cost efficiency and farmer welfare. The limitation of this study is that it only partially analyzes the production costs of white copra, while farmers need more profitable production cost information comparing white copra with smoked copra.